Variable-Intensity Simulated Team-Sport Exercise Increases Daily Protein Requirements in Active Males - Packer, Jeffrey E.; Wooding, Denise J.; Kato, Hiroyuki; Courtney-Martin, Glenda; Pencharz, Paul B.; Moore, Daniel R. (Frontiers in Nutrition, 2017)
Protein requirements are generally increased in strength and endurance trained athletes relative to their sedentary peers. However, less is known about the daily requirement for this important macronutrient in individuals performing variable intensity, stop-and-go type exercise that is typical for team sport athletes. The objective of the present study was to determine protein requirements in active, trained adult males performing a simulated soccer match using the minimally-invasive indicator amino acid oxidation (IAAO) method. After 2-d of controlled diet (1.2 g·kg-1·d-1 protein), seven trained males (23 ± 1 years; 177.5 ± 6.7 cm; 82.3 ± 6.1 kg; 13.5% ± 4.7% Body Fat; 52.3 ± 5.9 ml O2·kg-1·min-1; mean ± SD) performed an acute bout of variable intensity exercise in the form of a modified Loughborough Intermittent Shuttle Test (4x15 min of exercise over 75 min). Immediately after exercise, hourly meals were consumed providing a variable amount of protein (0.2-2.6 g·kg-1·d-1) and sufficient energy and carbohydrate (6 g·kg-1·d-1 ). Protein was provided as a crystalline amino acids modeled after egg protein with the exception of phenylalanine and tyrosine, which were provided in excess to ensure the metabolic partitioning of the indicator amino acid (i.e. [1-13C]phenylalanine included within the phenylalanine intake) was directed towards oxidation when protein intake was limiting. Whole body phenylalanine flux and 13CO2 excretion (F13CO2) were determined at metabolic and isotopic steady state from urine and breath samples, respectively. Biphasic linear regression analysis was performed on F13CO2 to determine the estimated average requirement (EAR) for protein with a safe intake defined as the upper 95% confidence interval. Phenylalanine flux was not impacted by protein intake (P=0.45). Bi-phase linear regression (R2 = 0.64) of F13CO2 resulted in an EAR and safe intake of 1.20 and 1.40 g·kg-1·d-1 , respectively. Variable intensity exercise increases daily protein requirements compared to the safe intake determined by nitrogen balance (0.83 g·kg-1·d-1) and IAAO (1.24 g·kg-1·d-1) but is within the range (i.e. 1.2-2.0 g·kg-1·d-1) of current consensus statements on general recommendations for athletes.